Environment operational performance effect on costs of capital structure financing of the Nigerian listed manufacturing companies - Abba, Magaji; Moh’d Said, Ridzwana; Abdullahi, Amalina; Mahat, Fauziah (Macrothink Institute, 2017)
Environmental performance of the Nigerian companies has become an issue of interest due to the negative effect of the companies' operations to the natural environment. The performance affects costs of capital structure financing because of its risk implication. Thus, the study examined the performance effect on costs of capital structure financing. Unlike the resource-depletion view of the performance, it is posited that environment operational performance lowers the companies’ costs of capital structure financing. With analysis of 53 listed companies from Nigerian Stock Exchange Market, negative effects are found between the environment operational performance and costs of capital structure financing of the companies. This aligned with instrumental stakeholder's theory of favourable resource allocation arising from improved environmental performance. It contributed to the understanding of capital structure financing advantage that can be achieved with environmental performance, thus supported the win-win view of corporate environmental performance.